Intergenerational educational mobility: The role of noncognitive skills - Anna Adamecz-Völgyi; Morag Henderson; Nikki Shure (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
While it has been shown that university attendance is strongly predicted by parental education, we know very little about why some potential 'first in family' or firstgeneration students make it to university and others do not. This paper looks at the role of non-cognitive skills in the university participation of this disadvantaged group in England. We find that conditional on national, high-stakes exam scores and various measures of socioeconomic background, having higher levels of non-cognitive skills, specifically locus of control, academic self-concept, work ethic, and self-esteem, in adolescence is positively related to intergenerational educational mobility to university. Our results indicate that having higher non-cognitive skills helps potential first in family university students to compensate for their relative disadvantage, and they are especially crucial for boys. The most important channel of this relationship seems to be through educational attainment at the end of compulsory schooling.
Keywords: I24; J24; 330; socioeconomic gaps; intergenerational educational mobility; higher education; non-cognitive skills